Analysis of Average Stock Prices and Average Liquidity of Shares Before and After a Stock Split on the Indonesian Stock Exchange 2002-2007 Period - Gilang Jatnika Barnas (Indonesia Auditing Research Journal, 2021)
This paper is going to explain the effect of stock split to stock price and stock liquidity. The objective of stock split is to make the stock in the optimum trading range. By doing a stock split, the demand for stock will increase so that trading volume will become liquid. After the stock split, the stock price will be higher than before if a positive signal about a better condition of management performance has been proven. This research aims to find the effect of stock split to stock price and stock liquidity of companies which did stock split in Indonesian Stock Exchange in the period 2002-2007. Based on paired sample t test, the result is shown that there is a significant difference between the mean of stock price before and after stock split. It is shown by the increasing stock price. Based on the TVA test